Racketeering in Campania: how clans have adapted and how the extortion phenomenon is perceived. Issue 1 (2nd January 2016) - Di Gennaro, Giacomo
Abstract : Institutional studies on the Camorra and its illegal activities are much more limited in comparison to the Sicilian Mafia. The study of its various aspects remains marginal, even though, through the first decade after the unification of Italy, the Neapolitan Camorra, as a form of organised crime and its associates, and not the Sicilian Mafia, raised initial concerns from the emerging national State. Illegal activities of the Camorra are developed on the illegal and legal market. This paper analyses the phenomenon of racketeering because it is not possible to understand the historical transformation of the essential traits of racketeering or the persistence of it if the birth, transformation and development of the Camorra are not reconstructed. Extortion is to the Camorra what territory is to the Mafia.